2006
DOI: 10.1103/physrevb.74.140101
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of light-induced first-order phase transformation in molecular solids:Fe(btr)2(NCS)2H2O

Abstract: The mechanism and kinetics of the thermally and light-induced spin transition of the highly cooperative spin crossover material Fe͑btr͒ 2 ͑NCS͒ 2 •H 2 O ͑btr= 4,4 Ј-bis-1,2,4-triazole͒ have been investigated by single crystal x-ray diffraction techniques. The key role of like-spin domains is quantitatively analyzed through a nucleation, growing, and coarsening mechanism whose kinetics follow the Kolmogorov-Johnson-Mehl-Avrami model with low dimensional characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 20 publications
2
31
0
Order By: Relevance
“…The dynamics of like-spin-domain nucleation and growth for heterogeneous cooperative transitions has indeed been determined using kinetic thermo-and photocrystallographic techniques. [64][65][66] In the following, we analyze successively the effect of a rapid quench cooling from room temperature to 10 K, the LS→HS photoexcitation process, and the subsequent HS→LS relaxation regime.…”
Section: Resultsmentioning
confidence: 99%
“…The dynamics of like-spin-domain nucleation and growth for heterogeneous cooperative transitions has indeed been determined using kinetic thermo-and photocrystallographic techniques. [64][65][66] In the following, we analyze successively the effect of a rapid quench cooling from room temperature to 10 K, the LS→HS photoexcitation process, and the subsequent HS→LS relaxation regime.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, it has been shown that the HS ↔ LS transition is related to a domain nucleation, growth and coarsening process in the solid state, with an unprecedented light-induced structural reorganization. [20,23] We report here a detailed structural analysis of [Fe(btr) 2 -(NCS) 2 ]·H 2 O in various spin states, HS-1, LS, HS-2q, HS2p, by using X-ray diffraction measurements performed at two temperatures, 15 K and 130 K (Figure 1). The main goal of this study is the characterization of the structural reorganization related to the light-induced and thermally induced spin transitions independent of thermal contraction/expansion effects.…”
Section: (Ncs) 2 ] (Pm = N-2ј-pyr-mentioning
confidence: 99%
“…6(a)] and the light-induced hysteresis reported in different system. 31,32,34,41,54 In BIA II, a gradual and homogeneous variation of the spin state is associated with the progressive motion of the Bragg reflections from a purely HS lattice to a purely LS one [see Fig. 6(d)]; such a homogeneous relaxation was observed in another low cooperative spin crossover complex by neutron diffraction.…”
Section: Cooperativity During the Photoconversions And Relaxationsmentioning
confidence: 99%